2002
DOI: 10.1213/00000539-200201000-00003
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Three Different Analgesia Techniques on Long-Term Postthoracotomy Pain

Abstract: Preoperatively initiated thoracic epidural analgesia has the most satisfying results in controlling postthoracotomy pain in the acute and long-term period, and it is associated with a decreased incidence (and intensity) of chronic pain compared with postoperative (epidural or IV) analgesia. Chronic pain has an incidence of 62%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
120
2
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 331 publications
(126 citation statements)
references
References 8 publications
2
120
2
1
Order By: Relevance
“…1,[4][5][6][7] The International Association for the Study of Pain defines PTPS as pain that recurs or persists along a thoracotomy scar longer than 2 months after surgery. 2,[4][5][6][7][8][9][10][11] The syndrome is thought to be predominantly of neuropathic origin, 1,9,12 secondary to damage to the intercostal nerves, causing neuralgia, but also caused by myofascial pain. 13 Many risk factors have been implicated and include genetic susceptibility, young age, female sex, pain before surgery, severe acute postoperative pain, and high postoperative opioid consumption.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1,[4][5][6][7] The International Association for the Study of Pain defines PTPS as pain that recurs or persists along a thoracotomy scar longer than 2 months after surgery. 2,[4][5][6][7][8][9][10][11] The syndrome is thought to be predominantly of neuropathic origin, 1,9,12 secondary to damage to the intercostal nerves, causing neuralgia, but also caused by myofascial pain. 13 Many risk factors have been implicated and include genetic susceptibility, young age, female sex, pain before surgery, severe acute postoperative pain, and high postoperative opioid consumption.…”
Section: Methodsmentioning
confidence: 99%
“…2). Patients in the placebo group had their chest tubes and epidural catheter removed earlier than patients in the pregabalin group (4 days [3][4][5] vs 5 days [3][4][5][6], respectively; P = 0.03). Intravenous equivalent hydromorphone consumption was comparable between groups, except at 96 hours where it was significantly lower for the pregabalin group.…”
Section: Immediate Postoperative Periodmentioning
confidence: 99%
“…35 Research is needed on whether the implementation of these guidelines for the treatment of patients with persistent postoperative pain will be therapeutically effective and if this approach will prevent the progression to chronic pain. Several studies suggest that perioperative epidural administration of bupivacaine and morphine can reduce the risk of transi-Downloaded by [Nanyang Technological University] at 07: 25 25 August 2015 tioning from acute to chronic pain in patients undergoing thoracotomy (at 6 months) 49 or requiring iliac donor crest harvesting (at 12 weeks). 50 Similarly, in patients undergoing breast surgery, preoperative subcutaneous bupivacaine reduced the occurrence of chronic pain at 1 year.…”
Section: Multimodal Postoperative Pain Managementmentioning
confidence: 99%
“…Three studies document that use of continuous thoracic-epidural analgesia in the perioperative period is associated with a decreased prevalence of pain at 6 months. [84][85][86] Two of these studies compared preincisional epidural local anesthetics to postincisional dosing; both studies found less acute postoperative pain and less chronic pain with preincisional dosing. Continuous thoracic paravertebral block has been reported to achieve superior or equivalent postoperative analgesia when compared with epidural analgesia, but long-term follow-up studies on chronic-pain prevalence have not been published.…”
Section: Literature Searchmentioning
confidence: 99%